ESTRUTURA E COMPOSIÇÃO DO COMPONENTE ARBÓREO DE UM FRAGMENTO FLORESTAL URBANO EM MUNDO NOVO, MS - Batista, Douglas; Carnevali, Natália; Vieira, Eliane; Souza, Daniela; Carnevali, Tiago; Abelha, Milza (ANAIS DO ENIC, 2018)
-